ECOTOURISM POTENTIAL IN UZBEKISTAN'S DOMESTIC TOURISM AND DEVELOPMENT PROSPECTS (Ustozlar uchun, 2026)
This article analyzes Uzbekistan\’s ecotourism potential and future development prospects. The study considers the country\’s natural resources, nature reserves, and national parks as key factors for ecotourism development. It also discusses ecotourism\’s contribution to environmental protection, employment for local communities, and economic growth as part of a sustainable tourism model. In addition, the paper identifies obstacles to ecotourism development and proposes forward-looking recommendations based on international experience. The research has both scientific and practical significance and may support the formation of tourism policy in the ecotourism domain.